Diagnostic accuracy of VIA and HPV detection as primary and sequential screening tests in a cervical cancer screening demonstration project in India. Issue 4 (12th February 2015) - Basu, Partha; Mittal, Srabani; Banerjee, Dipanwita; Singh, Priyanka; Panda, Chinmay; Dutta, Sankhadeep; Mandal, Ranajit; Das, Pradip; Biswas, Jaydip; Muwonge, Richard; Sankaranarayanan, Rengaswamy
<x xml:space="preserve">Abstract</x> Visual inspection after acetic acid application (VIA) and human papillomavirus (HPV) detection tests have been recommended to screen women for cervical cancer in low and middle income countries. A demonstration project in rural India screened 39, 740 women with both the tests to compare their accuracies in real population setting. The project also evaluated the model of screening women in the existing primary health care facilities, evaluating the screen positive women with colposcopy (and biopsy) in the same setup and recalling the women diagnosed to have disease for treatment at tertiary center. Accuracy of VIA and HPV test used sequentially was also studied. VIA was performed by trained health workers and Hybrid Capture II (HC II) assay was used for oncogenic HPV detection. Test positivity was 7.1% for VIA and 4.7% for HC II. Detection rate of CIN 3+ disease was significantly higher with HC II than VIA. Sensitivities of VIA and HC II to detect 162 histology proved CIN 3+ lesions were 67.9 and 91.2%, respectively after adjusting for verification bias. Specificity for the same disease outcome and verification bias correction was 93.2% for VIA and 96.9% for HC II. Triaging of VIA positive women with HPV test would have considerably improved the positive predictive value (4.0 to 37.5% to detect CIN 3+) without significant drop in sensitivity. All VIA positive women and 74.0% of HC II positive women had colposcopy. There was high compliance to treatment and significant stage‐shift of the screen‐detected cancers towards more early stage.